Implementasi Hukum Kebendaan Dan Hak Cipta Pada Penyelenggaraan Nft Di Indonesia - Aprilia, Aurel; Urbanisasi, Urbanisasi (Jurnal Ilmiah Wahana Pendidikan, 2023)
The current era of digitalization has had an impact on everyday human life. One of them is in the manufacture and sale and purchase transactions of assets and works of art which can now be done digitally. By being able to carry out NFT buying and selling transactions, NFT can be categorized as an object based on the rules contained in book II of the Indonesian Civil Code concerning Goods. Since NFTs are digital, they are categorized as intangible and movable objects. In addition, NFTs can also create property rights, have economic value, and can be transferred. With these characteristics, the NFT also meets the requirements of being an "object".The purpose of this research is to examine the position of these digital assets and works in the material law in Indonesia as well as the existence of intellectual property rights attached to the creators or copyright holders.